Associations of Serum Dickkopf‐1 and Sclerostin With Cardiovascular Events: Results From the Prospective Bruneck Study. Issue 6 (March 2020) - Klingenschmid, Gerhard; Tschiderer, Lena; Himmler, Gottfried; Rungger, Gregorio; Brugger, Stefan; Santer, Peter; Willeit, Johann; Kiechl, Stefan; Willeit, Peter
Abstract : Background: Dickkopf‐1 and sclerostin have been implicated in atherosclerosis and vascular calcification. We aimed to quantify the association of their serum levels with incident cardiovascular disease (CVD) in the general population. Methods and Results: Among 706 participants of the prospective, population‐based Bruneck Study, mean±SD of serum levels were 44.5±14.7 pmol/L for dickkopf‐1 and 47.1±17.5 pmol/L for sclerostin. The primary outcome was a composite CVD end point composed of ischemic or hemorrhagic stroke, transient ischemic attack, myocardial infarction, angina pectoris, peripheral vascular disease, and revascularization procedures. Over a median follow‐up duration of 15.6 years, 179 CVD events occurred. For the primary CVD outcome, multivariable‐adjusted hazard ratios (HRs) per SD higher level were 1.20 for dickkopf‐1 (95% CI, 1.02–1.42; P =0.028) and 0.92 for sclerostin (95% CI, 0.78–1.08; P =0.286). Secondary outcome analyses revealed that the association of dickkopf‐1 was primarily driven by ischemic and hemorrhagic stroke (67 events; HR, 1.37; 95% CI, 1.06–1.78; P =0.017), whereas no increase in risk was observed for transient ischemic attack (22 events; HR, 0.87; 95% CI, 0.53–1.44; P =0.593), myocardial infarction (45 events; HR, 1.10; 95% CI, 0.78–1.54; P =0.598), or for other CVD (45 events; HR, 1.25; 95% CI, 0.88–1.76; P =0.209). Conclusions: In this prospective, population‐based study, elevated baseline levels of dickkopf‐1, but not sclerostin, were independently associated with incident cardiovascular events, which was mainly driven by stroke. Our findings support the hypothesis of a role of dickkopf‐1 in the pathogenesis of CVD.